2019
DOI: 10.1001/jamacardio.2019.2974
|View full text |Cite
|
Sign up to set email alerts
|

Association of Multifaceted Mobile Technology–Enabled Primary Care Intervention With Cardiovascular Disease Risk Management in Rural Indonesia

Abstract: IMPORTANCE Cardiovascular diseases (CVDs) are the leading cause of disease burden in Indonesia. Implementation of effective interventions for CVD prevention is limited.OBJECTIVE To evaluate whether a mobile technology-supported primary health care intervention, compared with usual care, would improve the use of preventive drug treatment among people in rural Indonesia with a high risk of CVD. DESIGN, SETTING, AND PARTICIPANTSA quasi-experimental study involving 6579 high-risk individuals in 4 intervention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 28 publications
0
75
0
1
Order By: Relevance
“…This study also only evaluates the effect of training and education on the knowledge after interactive education and training, rather than its real impact on hypertension in the community. Therefore, future studies should be done using more samples from various locations to evaluate the benefit of hypertension knowledge improvement in the women cadre toward public awareness of hypertension and willingness to control their lifestyle and compliance with hypertension treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…This study also only evaluates the effect of training and education on the knowledge after interactive education and training, rather than its real impact on hypertension in the community. Therefore, future studies should be done using more samples from various locations to evaluate the benefit of hypertension knowledge improvement in the women cadre toward public awareness of hypertension and willingness to control their lifestyle and compliance with hypertension treatment [23].…”
Section: Discussionmentioning
confidence: 99%
“…The community-based management of hypertension in Nepal (COBIN) cluster randomized controlled trial in the general adult population of Nepal, established the effectiveness of a CHW-led home-based health education and screening for the reduction of Systolic BP (of almost 5 mmHg), in adults with hypertension; and amelioration of age-related increases in BP in adults without hypertension (52). Further examples of community-based programmes with potential to reduce cardiovascular risk in LMIC settings exist (53)(54)(55)(56), however as the COBIN trial team concluded; long-term trials with hard clinical outcomes, such as myocardial infarction and stroke as primary endpoints are needed to confirm the effect of CHW-led interventions on cardiovascular mortality and morbidity (52). Important areas for future research would be to conduct adequately sized, robustly designed trials, demonstrating tangible impact upon mortality across the lifecourse, including cost effectiveness analyses, and exploration of the impact of climate change and seasonal variations on BPrelated endpoints (57,58).…”
Section: Task-sharing In the Communitymentioning
confidence: 99%
“…In 2016, CVD accounted for a third of all deaths in Indonesia. 88 The government developed a policy for preventing and managing CVD through advocacy, health promotion, and health system strengthening particularly at district health agencies. Systematic Medical Appraisal Referral and Treatment (SMARThealth)-a multifaceted mobile technology-supported primary healthcare interventions was evaluated in populations from eight rural villages in Indonesia.…”
Section: Case Studymentioning
confidence: 99%
“…Systematic Medical Appraisal Referral and Treatment (SMARThealth)-a multifaceted mobile technology-supported primary healthcare interventions was evaluated in populations from eight rural villages in Indonesia. 88 The mobile application enabled primary healthcare nurses and physicians and community healthcare workers to collect patient information using basic equipment, assess individuals' risk status, receive tailored decision support, provide lifestyle advice and refer high-risk individuals to nurses and physicians. Use of SMARThealth interventions led to a significantly greater proportion of high-risk rural Indonesian population achieving systolic BP target <140 mmHg than those without the intervention (31.0% vs 22.2%, adjusted relative risk 1.3; 95%CI: 1.2-1.5; p<0.001).…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation